Two isopentenyl resorcinols from Peperomia tetraphylla. Issue 9 (2nd September 2021) - Lu, Xuan; Wang, Xin-Xue; Feng, Bao-Min; Zhang, Yang; Yu, Da-Yong; Shi, Li-Ying
Abstract: Two isopentenyl resorcinols, peperobtusin B and peperobtusin C, have been isolated from Peperomia tetraphylla . Their structures were determined on the basis of spectroscopic methods, especially 1 H NMR, 13 C NMR, 2D NMR, and HR-TOF-MS. Two compounds were evaluated for cytostatic activity against G2, A 549, Hela and HCT 116 cells, but cytostatic activity of both compounds is weak. Graphical abstract: UF0001